Cardiotoxic effect of bleomycin with a single administration in the experiment - Bestanchuk, E.; Gozhenko, A.; Kashchenko, O.; Narbutova, T.; Berezovskyi, O.; Zаkharova V. (Journal of Education, Health and Sport, 2021)
The aim of the study was to evaluate the effect of a single injection of bleomycin on the heart Material and methods. The study was conducted in the Research Institute of Transport Medicine during 2016-2021. The experimental model of the cardiotoxic effect of the bleomycin was performed using the medication "Bleocin" manufactured by Nippon Kayaku Co., Ltd. (Japan). According to the task, the study was performed on 10 mature rats of both sexes of the Wistar line with a body weight of 237 ± 20 g. Rats were housed in standard vivarium conditions of Odessa National Medical University. Animals were divided into 2 groups: experimental group (n = 5) and control (n = 5). Bleomycin animals of the experimental group were obtained intraperitoneally at a dose of 0.5 IU / kg once. Withdrawal of animals from the experiment was performed on the 5th day of the experiment, followed by morphological and morphometric examination. Statistical processing of the obtained data was performed by methods of variance, correlation and regression analysis using Statistica 14.0 software (TIBCO, USA) Results. Single administration os bleomycin causes changes in macroscopic parameters (myocardial weight, visual changes) are minimal. The main changes at the microscopic level are represented by contractural degeneration with segmental and / or partial-lateral lysis, ie there is not total but partial myocardial damage. Conclusion. A single injection of bleomycin can cause inflammatory-dystrophic changes of the myocardium.